Black woods, blue sky : a novel [large type] - Ivey, Eowyn (Random House Large Print, 2025)
"Birdie splits her days between caring for her six-year-old daughter Emaleen and working as a waitress at a roadside lodge in Alaska. But a soft-spoken recluse--adopted as a boy under mysterious circumstances by a local couple who raised him as their own but understood that he could never fully fit into their world. He calls the mountains on the far side of the Wolverine River his home and lives completely off the grid, appearing in the town at random intervals. But when he shows up at Birdie's lodge one day and she serves him honey and tea, the two form a friendship, and as they eventually fall in love Birdie begins to imagine a different life for herself and her daughter"--